Women in Tech: Rebuilding the link between librarians and farmers - Were, Jacinta (Technical Centre for Agricultural and Rural Cooperation, 2015)
Open data may not just be figures or indicators, but metadata describing documents. Jacinta Were describes how African libraries should not be sidelined in the efforts to make more open data available and that open access documents are an important resource in the data revolution for agriculture.